Rockburst mitigation mechanisms of pressure relief borehole and rock bolt support: Insights from granite true triaxial unloading rockburst tests - Ren, Fuqiang; Zhu, Chun; Karakus, Murat; He, Manchao (Engineering geology, 2024)
The construction of the deep-buried tunnels of the Sichuan-Tibet railway is facing severe rockburst disasters. Pressure relief boreholes and rock bolt support are effective methods for mitigating rockburst in hard rock. However, the mechanisms and differences in control effectiveness of these methods for different types of rockburst have yet to be revealed. This paper presents the results of two true triaxial unloading rockburst tests: Static-driven rockburst (static tests) due to excavation disturbance and dynamic-triggered rockburst (dynamic tests) due to adjacent tunnel excavation. The rockburst samples include intact granite, granite with a borehole (hole-granite), and granite with a negative Poisson's ratio bolt (bolt-granite). The mitigation mechanisms of the borehole and bolt were investigated in terms of rockburst intensity, failure patterns, and acoustic emission precursors. The results show that borehole and bolt inhibit the formation of a shear fracture plane during rockburst, with the bolt's inhibition effect being more pronounced. For static tests, borehole and bolt significantly reduce rockburst intensity, with the reduction being more significant for bolt-granite. The bolt mainly inhibits the propagation and penetration of shear microcracks. In contrast, the borehole promotes the propagation of shear microcracks. However, for dynamic tests, the rockburst intensity of bolt-granite is equivalent to that of intact granite, while the borehole enhances the rockburst intensity. The bolt inhibits the final buckling crack penetration in dynamic tests, while the borehole promotes slabbing. For static and dynamic tests, the borehole has little influence on precursor indicators, while the bolt increases the difficulty of precursor capture. Generally, the pressure relief borehole is more effective in controlling static tests, while bolt-reinforced support has advantages in dynamic test control. •Rockburst mitigation mechanisms using stress relief borehole and rock bolt support were revealed.•Static and dynamic rockburst tests were conducted on intact granite, hole-granite, and bolt-granite.•Pressure relief borehole is more effective in controlling static tests.•Boreholes and NPR bolts inhibit the formation of shear fracture during rockburst.•The borehole does not influence the optimal AE precursor, but the bolt increases the difficulty of capturing it.